The extent and determinants of precarious employment in Europe. Issue 1 (4th April 2016) - Kretsos, Lefteris; Livanos, Ilias
Abstract : Purpose: – The purpose of this paper is to investigate the extent and determinants of the so-called precarious employment across Europe and using different measures and based on individual's self-assessment. Design/methodology/approach: – Data on over two million workers across Europe (EU-15) from the European Union Labour Force Survey are utilised and a Heckman selection approach is adopted. Findings: – About one tenth of the total European workforce is in employment relationships that could be related to precariousness. The sources of precariousness are mainly involuntary part-time and temporary work. Less prominent as a source of precariousness is job insecurity related to fear of job loss. Vulnerable groups are found to have a higher risk of precariousness while significant country variations indicate that precariousness cannot be examined in isolation of the national context. Finally, signals of previous employment inability, such as lack of past working experience, as well as the state of labour market significantly increase the risk of precarious work. Originality/value: – The present study utilises a large-scale survey in order to investigate the incidence of precarious employment in a harmonised way and produce results that are comparable across EU-15 countries.